TINJAUAN KERAHASIAAN REKAM MEDIS ELEKTRONIK DI UPTD PUSKESMAS CIPAYUNG DEPOK - Sya'diah,SST,MKes., Yayah (APIKES Bhumi Husada Jakarta, 2024)
Confidentiality is essential for safeguarding data and information from unauthorized internal and external parties with regard to electronic medical records. Medical records are inherently private and must be protected by healthcare service personnel. Initial observations indicate that confidentiality measures have been ineffective due to the limitations and availability of features accessible to medical record officers, thereby compromising the confidentiality of electronic medical records. This study aims to assess the confidentiality of electronic medical records. A descriptive qualitative method was employed, utilizing observation and interview techniques for data collection. The study population consisted of the heads of medical records departments and medical record officers, using a saturated sampling method. The findings revealed that although Standard Operating Procedures for Medical Record Confidentiality are in place, they do not align with the Websimpusdin application system. The system lacks a codification feature for medical record officers, which impedes effective confidentiality. Consequently, the inability to use the coding feature without a doctor's account affects the assurance of electronic medical record confidentiality. At the Cipayung Depok Health Center, measures to facilitate the confidentiality of electronic medical records include restricting access for medical record officers and doctors and protecting information from unauthorized parties.. Keywords: Confidentiality, Electronic Medical Records (EMRs), Access Rights